Towards universal health coverage: Data for determinants of immunization coverage of Pneumococcal and Rota virus vaccines among under five children in Busolwe Town Council, Butaleja District, Eastern Uganda - Wafana Nabwana, Brenda; Namayanja, Sylvia Sidney; Kemigisha, Collette; Kisakye, Erina; Kuddiza Kusetula, Amos; Wakabi, Silvester; Wambi, Ivan; Musiime, Innocent; Nekaka, Rebecca; Gavamukulya, Yahaya (Data in brief, 2019)
The data described stipulates the factors influencing the immunization coverage of Pneumococcal and Rota Virus Vaccines among under five children (U5C) in Butaleja district in Eastern Uganda. The data was obtained in three major sections of demographic characteristics, knowledge, and attitude and perceptions of care takers of U5C on immunization. Both qualitative and quantitative types of data obtained from Primary and Secondary data sources are presented. The Primary sources included administration of questionnaires to the caretakers of U5C in communities surrounding different health centers in Butaleja district. The secondary source of datawas majorly the Health Management Information Systems (HMIS) records of Busolwe District Hospital. The data includes raw data from individual participants in form of Google forms portable document format, the consolidated raw data from all the participants in Microsoft excel format, as well as raw data from secondary HMIS record on immunization coverage in form of Microsoft excel format. The data provides a general outlook on the state of Butaleja district in terms immunization coverage of Pneumococcal and Rota Virus Vaccines.The data can be useful in taking action to decrease the burden of vaccine preventable diseases in Butaleja and elsewhere in similar settings.
Keywords: Immunization coverage; PCV; Rotavirus vaccine; Under five children (U5C)